Acceleration in temperature increase over India : An application of two-phase regression (MAUSAM, 2005)
A key issue in climate change is the extent to which there are changes in climate variables that may be consistent with anthropogenically induced climate change. In this paper an attempt has been made to apply two-phase regression model to records of long term annual mean surface air temperature over India to examine whether there are any significant changes in the temperature trends across the country. We find that most of the stations selected for the study, show an acceleration in temperature trends during the mid 1900’s. Even though a considerable variation with regard to the specific change point year is seen however there appear to be common periods across the different stations. Further analysis of long duration temperature records may be useful in attributing these changes to the anthropogenic forcing or natural variability.